2015
DOI: 10.1007/s00253-015-6710-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased riboflavin production by manipulation of inosine 5′-monophosphate dehydrogenase in Ashbya gossypii

Abstract: Guanine nucleotides are the precursors of essential biomolecules including nucleic acids and vitamins such as riboflavin. The enzyme inosine-5'-monophosphate dehydrogenase (IMPDH) catalyzes the ratelimiting step in the guanine nucleotide de novo biosynthetic pathway and plays a key role in controlling the cellular nucleotide pools. Thus, IMPDH is an important metabolic bottleneck in the guanine nucleotide synthesis, susceptible of manipulation by means of metabolic engineering approaches. Herein, we report the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 62 publications
(81 reference statements)
1
27
0
Order By: Relevance
“…Of all the metabolic engineering strategies tested, this was the most efficient in redirecting the metabolic flux of A. gossypii toward the production of inosine, allowing the obtainment of up to 2.2 g/L inosine in rich medium containing 40 g/L glucose. 9,12,13 Guanosine excretion was also increased in this strain (Dade12/ Dpnp1), but only by up to 2-fold. 13 In view of these results, A. gossypii became the first eukaryotic microorganism presenting good potential for the industrial production of inosine, which traditionally has been accomplished with B. subtilis and Escherichia coli modified strains.…”
Section: Nucleoside Productionmentioning
confidence: 79%
See 1 more Smart Citation
“…Of all the metabolic engineering strategies tested, this was the most efficient in redirecting the metabolic flux of A. gossypii toward the production of inosine, allowing the obtainment of up to 2.2 g/L inosine in rich medium containing 40 g/L glucose. 9,12,13 Guanosine excretion was also increased in this strain (Dade12/ Dpnp1), but only by up to 2-fold. 13 In view of these results, A. gossypii became the first eukaryotic microorganism presenting good potential for the industrial production of inosine, which traditionally has been accomplished with B. subtilis and Escherichia coli modified strains.…”
Section: Nucleoside Productionmentioning
confidence: 79%
“…Although the industrial production of riboflavin has come a long way, the recent advances in the field of systems biology for A. gossypii 2,[4][5][6][7] have shown that the carbon flux of this fungus toward riboflavin production can be further improved. 8,9 Moreover, the in silico modeling tools that recently became available for A. gossypii are also boosting the emergence of other commercially valuable biotechnological applications for this fungus, such as SCO production, 10 flavour compounds production [11][12][13] and also recombinant protein production 14,15 (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…The N-terminal tail of IMPDH, corresponding to residues 1-28 in IMPDH2, is the least conserved part of the protein, with large variation in length and sequence between phyla, as well as conformational variation among known structures (Fig. S3A) (Trapero et al 2018; Makowska-Grzyska et al 2015; Kim et al 2017; Prosise & Luecke 2003; Osipiuk et al 2014; Labesse et al 2013; Buey, Ledesma-Amaro, Balsera, et al 2015; Fernández-Justel et al 2019). The residues involved in filament contacts, however, are conserved among chordates, consistent with the fact that IMPDH polymerization has only been reported in vertebrates (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the triple mutants Dade12/Dimd3/DC631bas1 and Dade12/Dimd3/ P GPD -ade4 des also showed a marked reduction in inosine excretion Errors represent standard errors. c This strain has been previously described in Buey et al (2015) as DIMPDH or DIMD1. CDW stands for cell dry weight.…”
Section: Introductionmentioning
confidence: 99%
“…b This strain has been previously described in Ledesma-Amaro et al (2015). c This strain has been previously described in Buey et al (2015) as DIMPDH or DIMD1.…”
Section: Introductionmentioning
confidence: 99%